"Inhibiting inhibitors": Preliminary results of a new "DNA extraction-amplification" disinhibition technique in critical human samples. (December 2017) - Gomes, Cláudia; Alonso, Alejandro; Marquina, Domingo; Guardià, Marc; López-Matayoshi, César; Palomo-Díez, Sara; Perea-Peréz, Bernardo; Gibaja, Juan F.; Arroyo-Pardo, Eduardo
Abstract: The present study focused on the genetic analysis of a presumptive Bronze Age family burial, with at least six skeletons (Plana Castell, Barcelona, Spain). In order to investigate the individuals' biological affiliation, a molecular study was undertaken, but it was impossible to obtain a positive DNA amplification. The excavation data indicated that the skeletons were buried in an old location used as a dumping ground, being very likely the presence of biological and/or chemical contaminants. To overcome this difficulty, we undertook several modifications both in the extraction as in the amplification protocol, like MgCl2 concentration, or the inclusion of Bovine Serum Albumin (BSA). Despite their antiquity, the preliminary results indicate that all samples were effectively inhibited, and for the first time we were able to obtain mtDNA results, specifically, for the Hypervariable mitochondrial region 1. It also allowed us to infer that our protocol performance increased considerable, mainly the amplification modifications. In general, the best results were obtained with MgCl2 0, 6 μL (20 mM) and BSA 2 mg/mL per sample. Our result is quite important in a forensic analysis, mainly in cases where corpse/s is/are buried directly in the soil.